“The memory industry”: Reproduction and production of public stories about the Great Patriotic War - E. Α. Zakrevskaya; S. V. Belyanin (Шаги)
People who were eyewitnesses of the Great Patriotic War and have real memories have been playing an important role in preserving historical memory in USSR and Russia over the past decades. For instance, WWII veterans used to visit schools and tell children about their paths in the military, Nowadays, when the war is 80 years in our past, these people are passing away. However, the role of personal experience in war stories did not decrease due to the death if the eyewitnesses. In modern Russia there has grown a need for institutions for preserving and transmitting the memory of this war. In this article we will explore that “memory industry”. By that term we mean some institutionalized ways and practices aiming to reproduce — or even produce — personal stories about war. Nowadays veterans’ stories are published on the Internet, used to create vernacular or state museums, and as a base for patriotic upbringing of the youth. Such widespread use of personal stories from veterans and other adult eyewitnesses also affects stories told by the next generation: “the children of war”. Their memories cannot be substantive and in-depth due to their youth, so their stories often are unintentionally supplemented from the culture: folklore or media.